Analysis of Basketball Extracurricular Students Level of Interest in Terms of Intrinsic and Extrinsic Factors - Kelvin Triandi Renaldi; Abdul Rachman Syam Tuasikal (Center for Sports Science , Faculty of Sport Science, Universitas Negeri Padang, 2026)
Although previous studies have investigated students' interest in sports extracurricular activities, limited evidence is available regarding the simultaneous influence of intrinsic and extrinsic factors on participation in basketball extracurricular programs within a specific school context. This study aims to analyze the level of student interest in participating in basketball extracurricular activities at SMA Negeri 1 Gondang based on intrinsic and extrinsic factors and to examine differences in interest based on gender. This study used a quantitative method with a descriptive survey approach involving 25 students who were active participants in the basketball extracurricular program, selected using total sampling. Data collection was conducted using a questionnaire adapted from previous research. Data were analyzed using descriptive statistics, the Independent Samples t-test, Repeated Measures ANOVA, and the Bonferroni post-hoc test. The results showed that the average level of interest among male students (M = 2.508) was higher than that of female students (M = 2.454); however, there was no significant difference based on gender (p = 0.127). There was a significant difference in the intrinsic factors (F = 2.58; p = 0.011), with the interest factor being the most dominant. Additionally, there was a significant difference in the extrinsic factors (F = 61.80; p < 0.001), where the environmental and coach factors had the strongest influence on students’ interest. This study demonstrates that increasing student participation in basketball extracurricular activities requires strengthening intrinsic motivation, supported by a conducive school environment and effective coaching. The novelty of this study lies in its simultaneous analysis of intrinsic and extrinsic factors, as well as a gender-based comparison of students’ interest in participating in basketball extracurricular activities in the context of high school